Persepsi Masyarakat Kota Medan Terhadap Penggunaan Financial Technology - Tri Inda Fadhila Rahma (Universitas Islam Negeri Sumatera Utara, 2018)
This research aimed to find out the public perception of the use of financial technology (Fintech). The informant in this research is the citizen of Medan as a user fintech or not. Data collection techniques by using in-depth interviews to 10 informants with different ages and professions background. The analysis technique by using descriptive qualitative method that is useful to provide facts and data. The result shows that public perception toward the use of financial technology (fintech) includes attitude, interest, understanding, motivation, and expectation. Where attitude of society towards the use of fintech, providing support to the progress of financial technology innovation in Indonesia is very helpful for the community, while the public interest to use fintech has been proven from interviews 9 out of 10 respondents have been interested by using it. The society has understood the benefits and usage of fintech because using fintech is more efficient and effective than other financial services so that people are motivated to use fintech. The society hope to the organizers of fintech in order to provide socialization to the public and practicality in using the service, so that people who lack understanding of technology can use it easily.